Analisis faktor prioritas dan kriteria keberhasilan implementasi TQM pada industri module maker - Yayan Saputra; Sawarni Hasibuan (Operations Excellence: Journal of Applied Industrial Engineering, 2020)
The aim of this research is to determine the key success factors for the implementation of Total Quality Management (TQM) as the core of quality improvement in all elements of the module-making industry, which during the past five years did not have achieved the Key Performance Indicator (KPI) customer standard. In the initial stage, a literature review and previous research were carried out on critical success factors for the implementation of TQM in various sectors, then a Focus Group Discussion (FGD) was conducted to determine the structuring of the relationship between the success factors and the weight of the success factors for TQM implementation in the module maker industry using the Analytic method. Network Process (ANP). The main priority factors for the successful implementation of TQM in the module maker industry are the perspective of total organizational involvement, followed successively in the quality system perspective, the partnership perspective for customers & suppliers, the training & education perspective, and the measurement & information perspective. The most important criteria for each perspective are top management commitment, continuous improvement, focus on customer satisfaction, and performance measurement.